PERAN GURU KELAS DALAM MENGATASI KESULITAN BELAJAR SISWA SEKOLAH DASAR DI TENGAH PANDEMI COVID-19 - Zephisius Rudiyanto Eso Ntelok (JIPD (Jurnal Inovasi Pendidikan Dasar), 2021)
This study aims to examine the challenges and obstacles faced by elementary school classroom teachers in implementing the remote learning process and the efforts that classroom teachers can take to continue to meet the learning needs of elementary school students in the midst of the COVID-19 pandemic. The method used in this research is literature study by utilizing secondary data from previous research from scientific articles related to the topic being studied. The data were analyzed qualitatively by adopting the data analysis model from Miles and Hubermann. The results showed that distance learning during the COVID-19 pandemic experienced various obstacles, especially if it was based on online learning. These obstacles are in the form of technological inequality, digital competence, socio-economic conditions, difficulties in monitoring and evaluation as well as the increasing workload of teachers converting material into electronic form. However, there are several efforts made by elementary school teachers to overcome the learning difficulties of their students. In general, these solutions are divided into two broad groups, namely offline and semi-online. Offline is carried out with home visits / door to door, limited face-to-face learning according to schedule by implementing strict health protocols, and taking assignments to school so that they can still control student learning progress. Semi-online can be done by using the instant messaging application WhatsApp and the use of delayed video learning.